Sémantické preference intenzifikačních výrazů ve finštině - Zuzana Vorlíková (Časopis pro Moderní Filologii, 2023)
This paper investigates the phenomenon of intensification from the point of view of semantics. Specifically, such intensifiers, which by their meaning specify the degree of the property, at the same time exhibit other semantic features. In communication, they can express, for example, what kind of feelings a given utterance evokes in the speaker. The analysis of intensifiers and their collocates is performed on Finnish material. Two groups of intensifiers are compared with the finding that the semantic features of the intensifiers themselves affect their collocability; but apparently synonymous intensifiers also have different semantic preferences.